Relationship between Physical Activity Level and Body Mass Index among Active Students - Jayadilaga, Yadi; Handayani, Meliana (Science Tech Group, 2026)
Physical activity significantly impacts adolescent health, typically correlating with a normal Body Mass Index (BMI). This study aims to determine the relationship between physical activity levels and BMI among students. A cross-sectional study was conducted on 23 students at the FIKK UNM laboratory. Physical activity was assessed using the International Physical Activity Questionnaire-Short Form (IPAQ-SF), while BMI was calculated from digital scale and stadiometer measurements. Due to the small sample size, bivariate analysis was performed using the Fisher’s Exact Test. Results showed that most students engaged in heavy physical activity (47.8%) and had a normal BMI (47.8%). However, no significant relationship was found between physical activity levels and BMI (p > 0.05). Despite the lack of correlation, these findings support Sustainable Development Goal (SDG) Target 3.4, emphasizing the importance of monitoring young adults' physical activity and BMI as an early preventative measure to reduce premature mortality from non-communicable diseases (NCDs).